12. The Purpose of Empathy Formation and its Role in the Development of Modern Teachers from Primary Classes - Postolache Iulia (Sciendo, 2020)
The development of empathy is directly depended on the possibility of knowing the roles, establishing relationships, feeling emotions in different social situations. The functions of empathy allow an effective communication between teachers and students, strengthening mutual trust by analyzing their actions in the process of discussion. However, all these noted, can be achieved in the process of communication between the speaker and the listener, the teacher and the student. Empathy is characteristic to teachers who are able to think about their friend, not to be selfish. Empathetic teachers can feel what others feel, identify their emotions, help others to solve problems and imagine themselves in someone's situation. Empathetic teachers try to be in somebody's coat and realize what students would feel in certain situations. Empathy can be felt all the time and it's necessary to modern people, because everybody needs to accept himself and to respect others.